2015
DOI: 10.1002/lno.10104
|View full text |Cite
|
Sign up to set email alerts
|

Observations of tidal and storm surge attenuation in a large tidal marsh

Abstract: Tidal wetlands are increasingly valued for their role in coastal defense. Nevertheless, in situ observations of storm surge attenuation within wetlands are still scarce. We present water level measurements along a 4 km intertidal channel and on the surrounding marsh platform for regular spring to neap tides and two major storm surge tides, showing the effects of flood wave height and marsh geomorphology on the amount of flood wave attenuation. Undermarsh tides with peak water levels below marsh platform elevat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
88
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 81 publications
(97 citation statements)
references
References 28 publications
9
88
0
Order By: Relevance
“…These observations are in concordance with our findings and the lowest rates or water level amplifications were computed during the highest storm tides. We also observed that these effects could be a result of an increase in the storage area, a reduced bottom friction for higher water depths and lower friction exerted over the flow by the vegetation submergence in accordance with Stark et al ().…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…These observations are in concordance with our findings and the lowest rates or water level amplifications were computed during the highest storm tides. We also observed that these effects could be a result of an increase in the storage area, a reduced bottom friction for higher water depths and lower friction exerted over the flow by the vegetation submergence in accordance with Stark et al ().…”
Section: Resultssupporting
confidence: 92%
“…Similarly, moderate and major events revealed also a wide range of attenuation rates, especially at the MGB site. This wide variation was also observed by Stark et al () across their short non‐channeled transects (50–100 m) on the marsh platform in the Netherlands. Other studies performed on the East Coast of the U.S. such as van der Molen () found that the astronomical tide elevations were attenuated from −2 cm/km (amplification) to 11 cm/km over a larger tidal marsh (Item 10 in Table ).…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…Vegetated foreshores, such as salt marshes and mangroves are commonly occurring in deltaic systems where tides play a role in the sediment dynamics of the location [1,2]. These foreshores create additional safety against flooding, as they are able to reduce incoming wave energy and withstand erosive forces [3,4].…”
Section: Introductionmentioning
confidence: 99%